Aggregator control of battery energy storage in wind power stations to maximize availability of regulation service - James Boyle; Timothy Littler; Aoife M. Foley (Energy Conversion and Management: X)
Battery energy storage systems can produce very fast bi-directional power flows, which makes them suitable for providing wind power regulation and frequency control services. Though battery systems can provide fast regulation services, their energy storage capacities are quite low in comparison to other generation sources, so regulation responses from them should be optimized to maximize availability of service. This paper proposes an aggregator that optimizes frequency control responses from battery energy storage systems to maximize service availability. The frequency control response from the aggregated system is defined by a single frequency-droop characteristic. This provides the predictability of response required to comply with grid codes and allows the aggregated system to participate in frequency control markets as a single entity. The method of implementation is fail-safe as failure to receive an optimized order from the aggregator does not prevent the battery energy storage systems from responding to frequency events. This mitigates stability concerns relating to communication delays between the aggregator and battery energy storage systems. Battery systems that provide multiple functions, such as frequency control system services and wind power regulation, can participate in the aggregator scheme by assigning a proportion of the battery’s capacity to the aggregator scheme. Simulations performed in DIgSILENT PowerFactory show that the aggregator successfully extends the duration of full regulation service from the battery systems during frequency excursion events.